Comparative Study of PWM Control and PI Control of Induction Motor - Rohitash Singh; Saurabh Kr. Bajpai; Harinder Singh Sandhu (Bulletin of Electrical Engineering and Informatics, 2015)
The induction motor is without doubt the most used electrical motor because of its unique characteristics.  Most of its applications need fast and intelligent speed control system. This paper presents comparison of the intelligent and advanced speed control methods based on PWM technique and PI controller to achieve maximum torque and efficiency.  Simulation is carried out in MATLAB environment and results are investigated for speed control of induction motor without any controller and with PI controller on full load condition.